Relevant Issues of Standardisation of Herbal Drugs and Herbal Drug Preparations Containing Essential Oils - T. K. Ryazanova; V. A. Kurkin (Регуляторные исследования и экспертиза лекарственных средств)
Essential oils are a common group of bioactive compounds, yet their standardisation remains relevant.The aim of the study was to compare pharmacopoeial approaches to the standardisation of herbal drugs and herbal drug preparations containing essential oils using the examples of the State Pharmacopoeia of the Russian Federation (14th edition) and the European Pharmacopoeia (10th edition).The advantages of Russian pharmacopoeial approaches include testing for additional groups of bioactive compounds that contribute significantly to the pharmacotherapeutic effect of extractive preparations. The main compendial method for the component analysis of essential oils is gas chromatography with a flame ionisation detector; its limitations include the need for a considerable number of reference standards. The essential oil content limits established by the two pharmacopoeias for the same types of herbal drugs are not the same. The differences may be associated with differences in sample preparation conditions and analytical procedures for the determination of essential oil content, as well as with growth conditions of plants used to obtain data sets for the standardisation of this quality attribute. As a particular medicinal plant may have several chemotypes differing in the essential oil composition, it seems relevant to consider this composition in the studies of pharmacological activity of herbal drugs associated with essential oils.